THE MODERATING IMPACT OF PROFITABILITY ON CORPORATE SOCIAL RESPONSIBILITY (CSR) AND TAX AVOIDANCE RELATIONSHIP - Dewi Kusuma Wardani (AIBPM Publisher, 2018)
This study aims to determineThe Moderating Impact of Profitability on Corporate Social Responsibility (CSR) and Tax Avoidance Relationship. The population are manufacture companiessubsector food and beverage listed on the Indonesia Stock Exchange. We use purposive sampling method. We have 40 firm years. We use moderated regression analysis (MRA). We find that CSR has negative effect on tax avoidance and profitability strenghten that relationship. This research implies that the commitment of a company's social investment negatively impact the tax avoidance. Although companies have high social awareness, they will avoid tax when they are faced with financial constraint because of its low profitability. Keywords: Corporate Social Responsibility (CSR), tax avoidance, profitability, Global Reporting Initiative (GRI), cash effective tax rate (CETR), moderating, moderated regression analysis